Problems which Confront Renal Transplant Recipients - . Batool Amin (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The study objectives are to identify the problems which confront renal transplant recipients (RTRs). Methodology: ٨ descriptive study was carried out at two Teaching Hospitals with kidney transplant centers. Surgical specialties and Al-Karama outpatients’ clinics for ( RTRs) ,and three Teaching Hospitals; Medical city, Al-Karama and Al-Yermok which were responsible for immunosuppressive drugs distribution •Starting from October ,1 2006 ’؛ to the end of July 2OO7.T0 achieve the objectives of study, a non-probability (purposive) sample of 150 ( RTRs) who w ere attending to the outpatient clinic of the above listed hospital were selected according to the criteria of the study sample . The finalized questionnaire contained (83) items. The content validity of the instrument was established through penal of (14) experts. Reliability of the problems scales was determined by test-retest method which was estimated as average Data was gathered by interview technique using the questionnaire format and data was analyzed application of descriptive and inferential statistical methods. Results: The results of the study indicated that the ( RTRs) confront (83 ) problems and affected these problems with different severity level, high, moderate, and low. Recommendation: According to the results of this study, the researcher recommended that the provision of the necessary post transplant medicines from easy to reach centers.